Changes in Households’ Welfare and Consumption Patterns among Jenitri (Elaeocarpus ganitrus) Farmers in Kebumen Regency - Central Java - Tri Marini; Nurhadi Nurhadi; Yuhastina Yuhastina (Jurnal Mamangan, 2022)
This research aims at analyzing changes on the welfare level and consumption patterns among Jenitri (Elaeocarpus ganitrus) farmers in Pujotirto, Karangsambung, Kebumen regency of Centra Java- Indonesia. Using mix-method, this research combined quantitative method and that of qualitative. Quantitative data was collected by a survey involving 20 respondents which were selected purposively. Qualitative data was collected by a series of in-depth interviews with farmers and traders of jenitri. Quantitative data was analyzed descriptively. Interview data was transcripted and analyzed by using domain analysis technique. The research resulted in following conclusions: (1) the cultivation of jenitri has brought about significant changes in farmers’  welfare; (2) the raised welfare level affects the pattern of household’s consumption; (3) prior to cultivating jenitri, farmers’ household tend to be subsistence-oriented; (4) now that they cultivate jenitri, they are driven to meet secondary and tertiary needs, such as motorcycles and jewelries.